Factors associated with psychological disturbance among healthcare providers during the early phase of COVID-19 pandemic in Kelantan, Malaysia - Norhayati Mohd Noor; Ruhana Che Yusof; Mohd Azman Yacob (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
COVID-19 pandemic had significant emotional and psychological effects on the general population where healthcare providers were no exception. This study aimed to identify the factors associated with psychological disturbances such as vicarious traumatisation, anxiety and depression among healthcare providers during the early phase of the COVID-19 pandemic. This cross-sectional study included 306 participants who fulfilled the inclusion and exclusion criteria from May to July 2020 in a state tertiary hospital. We employed a self-administered case report form containing socio-economic data and three questionnaires, i.e. Malay version Vicarious Traumatization Questionnaire, Hospital Anxiety and Depression Scale and Medical Outcome Study Social Support Survey. Descriptive analysis and linear regression were applied for vicarious traumatisation while binary logistic regression was applied for anxiety and depression outcomes. The findings suggested that participants worked in the Medical Department were more likely to develop psychological disturbances than other departments. Non-frontline (adjusted coefficient [95% CI]: -17.04 [-24.77, -9.30]) and female healthcare providers (adjusted coefficient [95% CI]: 10.73 [2.99, 18.46]) were associated with vicarious traumatisation. Non-frontline healthcare providers (adjusted odds ratio [95% CI]: 0.13 [0.06, 0.29]) were also associated with anxiety besides shift work (adjusted odds ratio [95% CI]: 3.80 [1.04, 13.83]). Meanwhile, medical officers (adjusted odds ratio [95% CI]: 0.31 [0.10, 0.91]) were less likely to report depression symptoms compared to staff nurses. These findings can assist hospital bureaucracy to focus on necessary interventions to improve the mental and psychological health of healthcare providers.